The "world" of Ouyang Xiu's literary work: From the perspective of emotion - Seong, L.D. (2010)
There are numerous researches on the biography of Ouyang Xiu; however the focus on his inner emotion is scarce. In my point of view, this aspect is actually the focal point of his life and is strongly reflected in most of his writings; from his memory of mentors and friends, his remembrance on the places visited, his writing on history, to his collections of ancient bronzes and stone tablets, his emotion is always the crucial part of his reflection and value judgment. This emotional state evolved continuously at his different period of life and different stages of writings. It was undoubtedly affected by his maturity in age and life experience but his physical, psychological and temperament conditions are the more prominent affecting factors. As a result, we can find a gap between the "Ouyang Xiu" shown in the biography and Chinese literary history compared with the "Ouyang Xiu" enshrined in his literary work. This might due to the objectivity underlined in biography and the emotional subjectivity underlined in literary works. More interestingly, the former is about reality of life and the latter is about "world" of literary works, which is not an objective reality, but was actually organized and experienced by an individual subject. This theory is put forward by the phenomenological criticism in their grasping of the "deep structures" of the author mind, which can be found in recurrent themes and patterns of imagery. lIn other words, it is an attempt to grasp the way the writer "lived" his world. With this in mind, this paper aims to unravel the inner perception and emotions of Ouyang Xiu, with the hope that the more private self of the author could be revealed through his "world" in literature.